2023
DOI: 10.1021/acs.joc.3c00585
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Triarylsilanols as Catalysts for Direct Amidation of Carboxylic Acids

Abstract: Triarylsilanols have been reported as the first silicon-centered molecular catalysts for direct amidation of carboxylic acids with amines as identified after a screen of silanols, silanediols, disiloxanediols, and incompletely condensed silsesquioxanes as potential homogeneous catalysts. Subsequent synthesis and testing of various electronically differentiated triarylsilanols have identified tris(p-haloaryl)silanols as more active than the parent triarylsilanol, where the bromide congener is found to be the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 168 publications
0
7
0
Order By: Relevance
“…1). 7,20,31 To develop a robust automated method, we began by emulating the manual routine within a Python script that calculates the transformed time axis for a chosen reaction species and corresponding order value(s) using a selected subset of the kinetic data, tested on literature examples (see section S8). 28 Subsequently, a robust automatic method of assessing the overlay of reaction progress profiles https://doi.org/10.26434/chemrxiv-2024-ck8c5 ORCID: https://orcid.org/0000-0001-9920-2793 Content not peer-reviewed by ChemRxiv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 7,20,31 To develop a robust automated method, we began by emulating the manual routine within a Python script that calculates the transformed time axis for a chosen reaction species and corresponding order value(s) using a selected subset of the kinetic data, tested on literature examples (see section S8). 28 Subsequently, a robust automatic method of assessing the overlay of reaction progress profiles https://doi.org/10.26434/chemrxiv-2024-ck8c5 ORCID: https://orcid.org/0000-0001-9920-2793 Content not peer-reviewed by ChemRxiv.…”
Section: Methodsmentioning
confidence: 99%
“…1,2,3,4 Chemical kinetics is also utilized extensively to understand and optimize the behaviour of reaction systems, particularly complex catalytic reactions. [5][6][7][8][9] The global rate equation (a.k.a. the rate law) is a mathematical expression that correlates the rate of a reaction with the concentration of each reaction species, with the general form: A global rate equation can be constructed empirically from experimental data, without explicit considerations of the reaction mechanism or mass transfer effects.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20] Different stable monosilanols, silanediols and -triols are already described in literature, such as Ph 3 SiOH, [21] Et 3 SiOH, [21] (n-Bu) 3 SiOH, [21] (tert-BuO) 3 SiOH, [22] Me 2 Si(OH) 2 , [23] Ph 2 Si(OH) 2 , [24] (cis-C 6 H 11 ) 2 Si(OH) 2 , [25] (tert-Bu) 2 Si(OH) 2 , [10] (ortho-tolyl) 2 Si(OH) 2 , [26] (iso-propyl) 2 Si(OH) 2 [27] PhSi(OH) 3 , [28] c-C 6 H 11 Si(OH) 3 [29][30] and tert-BuSi(OH) 3 . [31] Silanediols have been already used, for example, in the synthesis of LED encapsulation resins and in pharmaceutical applications, [24,[32][33] monosilanols were applied as catalysts for various organic syntheses, such as cross coupling reactions [34][35][36] or direct amidation of carboxylic acid [37] and silanetriols have already been used for the synthesis of various metallasiloxanes [38][39] and POSS cages. [40][41][42] Many of the stable silanols are solid and crystalline at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the ACS Green Chemistry Institute Pharmaceutical Roundtable identified sustainable (direct) amide or peptide formation as a “key green chemistry research area”. 2 Silyl-based coupling reagents have been recently developed on this background, 3 with amide bond formation using hydrosilanes attracting considerable attention. Hydrosilanes have low toxicity.…”
mentioning
confidence: 99%
“…The previous report focusing on silicon-mediated amide bond synthesis suggested that the active intermediate was the silyl ester species. 3,5,6,11,18 We failed to separate any silyl ester species of amino acids but considered the mechanism of this reaction based on the abovementioned results (Scheme 5). First, the carboxy group of the amino acid was deprotonated by the amine, and the resulting carboxylate 5 attacked the silicon atom of hexylsilane, releasing hydrogen to form the silyl ester 6 .…”
mentioning
confidence: 99%